The correlation between autumnal landscape colors and environmental factors and the analysis of ecological service functions in subtropical urban scenic forests - Wang, Zi; Li, Mingyang (Frontiers in Forests and Global Change, 2024)
Background and Objectives: Urban scenic forest is a main component of forest parks, and a quantitative study of the landscape color of urban scenic forest can provide a scientific reference for the planning of forest parks and the design of scenic forest management measures. The purpose of the study is to find the quantitative correlation between autumn landscape color and ecological service functions, and obtain the important influencing factors. Materials and methods: This study uses Purple Mountain National Forest Park in Nanjing as a case study area and forest resource survey data from Purple Mountain National Forest Park in 2020, autumn landscape color photograph data from Purple Mountain National Forest Park in 2020, and digital elevation model data as the main information sources. The correlation between two ecological functions of above-ground biomass (AGB), tree species diversity (TSD) and influencing factors (includes color factors, stand factors, and terrain factors) were both analyzed by Pearson correlation analysis. Then, the multiple linear regression (MLR) and random forest (RF) two methods were used to perform the quantitative relationship between each other. Results: The results show: in the established quantitative models of AGB, TSD as the dependent variable, the correlation coefficients of MLR model are both above 0.784, while the correlation coefficients of RF model are all above 0.872. Moreover, the brightness value of the main color (BRI), the number of yellow-green blocks (NYG) and the number of yellow blocks (NY), the three color factors have important effects on the two ecological service functions. Conclusions: In conclusion, there are complex nonlinear relationships between the ecological service functions of AGB, TSD and influencing factors, and the landscape color can reflect the ecological function of the scenic forest to some extent. Besides, stand factors and color factors have important effects on the ecological function of AGB. Color factors and terrain factors have important effects on the ecological function of TSD. And BRI, NYG and NY three factors all have important effects on the two ecological functions. Finally, this quantitative method has universal applicability in the temperate zone, warm temperate zone and subtropical zone of China.